2005
DOI: 10.1590/s0004-282x2005000100008
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic tectal low grade astrocytomas: is surgical removal an alternative treatment? Long-term outcome of eight cases

Abstract: Low-grade gliomas arising in dorsal midbrain in children and young patients usually present few neurological symptoms and findings, and patients management is controversial. Some authors propose only clinical observation until the patient present signs of increased intracranial pressure when a shunt with or without biopsy, is inserted; others recommend radiotherapy after stereotactic or open biopsy. Microsurgical total removal of tumor may be curative. We present a retrospective analysis of eight patients (mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
23
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 48 publications
(54 reference statements)
0
23
0
Order By: Relevance
“…21 Tectal plate gliomas typically behave in a benign and indolent fashion, and only a small number will exhibit progression, result in new neurological symptoms, and require treatment including surgery, radiation therapy, and chemotherapy. 2,5,[13][14][15][20][21][22] The challenge in the management of tectal plate gliomas remains in the uncertainty of knowing which tumors will eventually exhibit clinically significant growth. In our study, 44 patients diagnosed with tectal plate glioma on MRI underwent follow-up clinically and radiologically for a mean of 7.6 years and 6.5 years, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…21 Tectal plate gliomas typically behave in a benign and indolent fashion, and only a small number will exhibit progression, result in new neurological symptoms, and require treatment including surgery, radiation therapy, and chemotherapy. 2,5,[13][14][15][20][21][22] The challenge in the management of tectal plate gliomas remains in the uncertainty of knowing which tumors will eventually exhibit clinically significant growth. In our study, 44 patients diagnosed with tectal plate glioma on MRI underwent follow-up clinically and radiologically for a mean of 7.6 years and 6.5 years, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Neurosurgical interventions have been described, but few references in the literature describe long-term outcome [3][4][5][6][7][8]. Those references that do discuss outcomes are small case series, suggesting that this lesion has an indolent, non-aggressive course [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Mesencephalic tectal glioma is a topographical diagnosis consisting of a heterogeneous group of gliomas in children, with relatively benign and indolent clinical course in most previous case reports (1–3, 5, 9–11). Although the histopathological features of this tumor are compatible with a diagnosis of mixed oligoastrocytoma, the FISH study showed that this tumor is negative for co‐deletion of chromosomes 1p and 19q.…”
Section: Discussionmentioning
confidence: 86%
“…As noted by most previous authors, appropriate management of pediatric tectal gliomas depends on the clinical symptoms as well as the histopathology of these tumors. Due to the relatively indolent clinical course of most pediatric tectal tumors, most authors advocate conservative treatments to manage hydrocephalus (1–3, 5, 7–11). However, rare high grade astrocytoma with aggressive clinical behavior also have been reported (6, 12).…”
Section: Discussionmentioning
confidence: 99%